La scienza non sarà più la stessa. Più condivisione, cooperazione e solidarietà dopo il CoViD-19? (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
We live in times of bewilderment and confusion. At times like these, it is not unusual to meet opinions about the future. It is perhaps an escape from the uncertainty of the present that grips us. Some voices have argued that humanity after the CoViD-19 pandemic will never be the same again. Optimists say that we will be better. The pessimists predict that we will repeat the mistakes of the past, aggravating them and opening the doors to a new threat for us, for the other species and for the planet. What about science?
Keywords: CoViD-19; pandemic emergency; intellectual property; Open Science; Open Access